Separate and Joint Associations of Shift Work and Sleep Quality with Lipids - Luenda E. Charles; Ja K. Gu; Cathy A. Tinney-Zara; Desta Fekedulegn; Claudia C. Ma; Penelope Baughman; Tara A. Hartley; Michael E. Andrew; John M. Violanti; Cecil M. Burchfiel (Elsevier, 2016)
Background: Shift work and/or sleep quality may affect health. We investigated whether shift work and sleep quality, separately and jointly, were associated with abnormal levels of triglycerides, total cholesterol (TC), and low-and high-density lipoprotein cholesterol in 360 police officers (27.5% women). Methods: Triglycerides, TC, and high-density lipoprotein were analyzed on the Abbott Architect; low-density lipoprotein was calculated. Shift work was assessed using City of Buffalo payroll work history records. Sleep quality (good, ≤ 5; intermediate, 6-8; poor, ≥ 9) was assessed using the Pittsburgh Sleep Quality Index questionnaire. A shift work + sleep quality variable was created: day plus good sleep; day plus poor sleep; afternoon/night plus good; and poor sleep quality. Mean values of lipid biomarkers were compared across categories of the exposures using analysis of variance/analysis of covariance. Results: Shift work was not significantly associated with lipids. However, as sleep quality worsened, mean levels of triglycerides and TC gradually increased but only among female officers (age- and race-adjusted p = 0.013 and 0.030, respectively). Age significantly modified the association between sleep quality and TC. Among officers ≥ 40 years old, those reporting poor sleep quality had a significantly higher mean level of TC (202.9 ± 3.7 mg/dL) compared with those reporting good sleep quality (190.6 ± 4.0 mg/dL) (gender- and race-adjusted p = 0.010). Female officers who worked the day shift and also reported good sleep quality had the lowest mean level of TC compared with women in the other three categories (p = 0.014). Conclusion: Sleep quality and its combined influence with shift work may play a role in the alteration of some lipid measures.